2019
DOI: 10.2169/internalmedicine.2804-19
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Biliary Intervention Using Traction Devices for Periampullary Diverticulum

Abstract: We describe the case a 92-year-old woman who was admitted to our hospital with choledocholithiasis and periampullary diverticulum (PAD). Due to PAD, clear visualization of the ampulla of Vater could not be obtained. Although selective bile duct cannulation was difficult, a 7-Fr plastic stent was placed during the first session. Fifteen days later, endoscopic retrograde cholangiopancreatography was retried using traction devices, and the papilla became visible. Endoscopic sphincterotomy and stone extraction wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Unlike conventional endoclips, the Sure-Clip is a device that can be easily used for clipping even when the forceps elevator of the duodenoscope is lifted. Previous reports have shown that the visi-bility of an intradiverticular papilla was improved when endoclips were used [3][4][5], but this is the first report in which the papilla was fixed and a long narrow distal segment was stretched using this newly designed clipping system. This method is simple and useful in cases where the papilla is unstable.…”
mentioning
confidence: 88%
“…Unlike conventional endoclips, the Sure-Clip is a device that can be easily used for clipping even when the forceps elevator of the duodenoscope is lifted. Previous reports have shown that the visi-bility of an intradiverticular papilla was improved when endoclips were used [3][4][5], but this is the first report in which the papilla was fixed and a long narrow distal segment was stretched using this newly designed clipping system. This method is simple and useful in cases where the papilla is unstable.…”
mentioning
confidence: 88%
“…Cases of difficult CBD intubation during ERCP have been reported 1 . The traction device (S-O clip) can also be used in complex cases with diverticular papillae during conventional ERCP 2 . CBD intubation using this device for diverticular papilla in Roux-en-Y reconstruction has also been reported 3 .…”
Section: Figmentioning
confidence: 99%
“…Periampullary diverticulum (PAD) is considered a risk factor for difficult biliary cannulation during endoscopic retrograde cholangiopancreatography (ERCP) because it makes the papilla unidentifiable 1 . Applying a traction force near the papilla has been reported to be effective in PAD biliary interventions 2 . We report a successful case of endoscopic hemostasis in post-sphincterotomy bleeding, using the multiloop traction method (M-loop method), in a patient with PAD 3 ( Video 1 ).…”
Section: Figmentioning
confidence: 99%